LANDSCAPE ATRIBUTES DERIVED FROM DIGITAL ELEVATION MODEL AND RELATIONSHIPS WITH SOILS - SIRTOLI, Angelo Evaristo; SILVEIRA, Claudinei Taborda da; MANTOVANI, Luiz Eduardo; SIRTOLI, Ana Rosa dos Anjos; OKA-FIORI, Chisato (Scientia Agraria, 2008)
The present study approaches the relationships between soils and attributes of the landscape derived from a digital elevation model (DEM) in a area over the Guabirotuba Formation formed by alluvial and secondary deposits colluvial fans deposits. Starting from the digital elevation model we did derived six primary landscape attributes: elevation, slope, global solar radiation, plan and profile curvature. A secondary attribute, the topographical index of humidity (TIW) was also created. The eventual interactions between the geology and the derived attributes of DEM with the soil mapped in the area were evaluated. The results showed that combination of the geology and TWI data can explain occurrence of Gleyssols and Histosols. The major soils formations were located in the following conditions: Ferralsols - plan landscape with curvature plan and profile, divergent and convex; Cambisols - convergent/divergent and concave; and the association Gleysols and Histosols convergent/planar and flat. The high degree slopes facing south presented matiz betwen 7,5 YR - 10 YR, yellowish soil color. The Ferralsols class and soils with hydromorphic character were located in flat landscape while Cambisols were situated in the largest steepness. The highest positions which represented well preserved soil again loss, had predominantly Ferralsols. The Cambisols were situated in intermediate positions and in the lowest altitudes were found soils of character hydromorphic.